The use of temporary external pacemaker to control surgically produced complete atrio-ventricular block during open heart surgery - Aytaç, Aydın; Tuncalı, Tahsin (The Turkish Journal of Pediatrics, 1967)
We have presented a case of ventricular septal defect with severe pulmonary hypertension in which total heart block developed during surgical repair. The rôle of pulmonary hypertension is discussed in the prognosis and surgery. Details of the management of surgically produced heart block occurring during the repair of a large ventricular septal defect are given and the rôle of the pacemaker in reducing the mortality from heart block is emphasized.